Cellular Dysfunction in Diabetes as Maladaptive Response to Mitochondrial Oxidative Stress. (2nd January 2012) - Naudi, Alba; Jove, Mariona; Ayala, Victoria; Cassanye, Anna; Serrano, Jose; Gonzalo, Hugo; Boada, Jordi; Prat, Joan; Portero-Otin, Manuel; Pamplona, Reinald
Abstract : Oxidative stress has been implicated in diabetes long-term complications. In this paper, we summarize the growing evidence suggesting that hyperglycemia-induced overproduction of superoxide by mitochondrial electron transport chain triggers a maladaptive response by affecting several metabolic and signaling pathways involved in the pathophysiology of cellular dysfunction and diabetic complications. In particular, it is our goal to describe physiological mechanisms underlying the mitochondrial free radical production and regulation to explain the oxidative stress derived from a high intracellular glucose concentration and the resulting maladaptive response that leads to a cellular dysfunction and pathological state. Finally, we outline potential therapies for diabetes focused to the prevention of mitochondrial oxidative damage.